Outcomes following first-episode psychosis: why we should intervene early in all ages, not only in youth - Lappin, Julia M.; Heslin, Margaret; Jones, Peter B.; Doody, Gillian A.; Reininghaus, Ulrich A.; Demjaha, Arsime; Croudace, Timothy; Jamieson-Craig, Thomas; Donoghue, Kim; Lomas, Ben; Fearon, Paul; Murray, Robin M.; et al. (SAGE Publications, 2016)
Objective: To compare baseline demographics and 10-year outcomes of a first-episode psychosis patient incidence cohort in order to establish whether current youth-focussed age-based criteria for early intervention services are justified by patient needs. The patients in this cohort were treated prior to the establishment of early intervention services. The study aimed to test the hypothesis that those who develop psychosis at a younger age have worse outcomes than those who develop psychosis at an older age. Methods: Data on first-episode psychosis patients from the ÆSOP-10 longitudinal follow-up study were used to compare baseline characteristics, and 10-year clinical, functional and service use outcomes between those patients who would and would not have met age-based criteria for early intervention services, in Australia or in the United Kingdom. Results: In total, 58% men and 71% women with first-episode psychosis were too old to meet current Australian-early intervention age-entry criteria (χ2 = 9.1, p = 0.003), while 21% men and 34% women were too old for UK-early intervention age-entry criteria (χ2 = 11.1, p = 0.001). The 10-year clinical and functional outcomes did not differ significantly between groups by either Australian- or UK-early intervention age-entry criteria. Service use was significantly greater among the patients young enough to meet early intervention age-criteria (Australia: incidence rate ratio = 1.35 [1.19, 1.52], p < 0.001; United Kingdom: incidence rate ratio = 1.65 [1.41, 1.93], p < 0.001). Conclusion: Current early intervention services are gender- and age-inequitable. Large numbers of patients with first-episode psychosis will not receive early intervention care under current service provision. Illness outcomes at 10-years were no worse in first-episode psychosis patients who presented within the age range for whom early intervention has been prioritised, though these patients had greater service use. These data provide a rationale to consider extension of early intervention to all, rather than just to youth.